THE “DECONSTRUCTION” AND “SYNAESTHESIA” IN CHOREOGRAPHIC COURSE ITS CONCEPTS AND PRACTICES, ITS EFFECTIVENESS - Li, Bin (European Journal for Philosophy of Religion, 2023)
This paper applies deconstruction and synaesthesia theory to the teaching of choreographic course in a professional discipline at university level, adopts the method of case study, explores the effective approach of movement form innovation, so that such exploration can be more unified: rationality and sensibility, objectivity and subjectivity. Deconstruction is more rational and objective; Synaesthesia is more perceptual and subjective.The purpose is to solve the singleness and boredom caused by the solidification of dance vocabulary and to provide a new pattern for the teaching reform of dance education.